'When he's in Afghanistan it's like our world/his world': mediating military experience. (January 2017) - Parry, Katy; Thumim, Nancy
This article reports on a qualitative research project which invited those with direct experience – as serving personnel involved in media operations, military veterans and forces family members – to respond to a variety of media genres and discuss how such portrayals of military experience correspond with their own perceptions and their own representational practices. It is our contention that such mediations offer significant and interconnected spaces through which to explore negotiations of the meanings of military experience in contemporary public culture. Drawing on thematic analysis from our focus groups, we address a number of research questions: In what ways do the participants identify and engage with the various media portrayals, and how do they think this relates to the perceived public profile of the armed forces? How do they assess the capability of media texts to provide insights into the 'realities' of military experience (including emotionally charged moments of camaraderie and trauma)? In the multiple challenges and ambiguities heard within our groups, we find complex and troubled senses of 'militariness', bound up with sometimes intense affectivities.